2008
DOI: 10.1088/0957-4484/20/2/025608
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented re-growth of carbon nanotubes onin siture-activated catalyst

Abstract: A simple-stepped growth process for the synthesis of carbon nanotubes that exhibit excellent field emission properties is reported. In the process, the growth was interrupted, and during the interruption the catalyst was re-activated in situ, resulting in enhanced growth of the CNTs after the interruption. A film of CNTs re-grows on top of an existing CNT film at much higher rates, which can be up to 669% higher. The tubular structure continues during the re-growth. The structural continuity creates an opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Owing to the numerous allotropic forms, various carbon materials, such as carbon nanotubes, carbon nanofibers, graphenes, and carbon coils have been synthesized [1][2][3][4]. A unique form of carbon material can provide the particular material characteristics needed for a specific use.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the numerous allotropic forms, various carbon materials, such as carbon nanotubes, carbon nanofibers, graphenes, and carbon coils have been synthesized [1][2][3][4]. A unique form of carbon material can provide the particular material characteristics needed for a specific use.…”
Section: Introductionmentioning
confidence: 99%
“…But, direct growth of CNTs on metal surfaces normally involves in-situ formation of catalyst nanoparticles on the metallic substrates [14,15] which is normally found to be difficult. Nevertheless, people have tried and there are some reports regarding this type of growth [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Talapatra et al [13] have grown vertically aligned CNTs on Inconel substrates using CVD process with ferrocene-xylene precursors and studied their properties for the applications as double-layer capacitors and field-emitter devices.…”
Section: Introductionmentioning
confidence: 99%
“…mA/cm 2 at the same value of the electric field. Ting et al [27] investigated field emission behavior of CNTs grown on Fe-Si thin films by a two-step growth process and found that catalyst particles got re-activated in the second step when they switched off the plasma and gas flow for some time and then again restored it for further growth of CNTs. Growth of CNTs have been reported by Yang et al [23] during the diamond deposition experiment using microwave plasma enhanced chemical vapor deposition (MPECVD) process.…”
Section: Introductionmentioning
confidence: 99%
“…The result was the fabrication of VA-CNTs with average heights of 182 mm and radii of 5 nm. [118] A very low turn on voltage (0.1 V mm…”
mentioning
confidence: 99%
“…[118] The big promise of these VA-MWCNT-based FE devices are applications which include FE displays, [119] X-ray tubes, [120] lighting filaments, [121] and plasma and microwave sources, [122] just to name a few. In particular, novel FE displays are fabricated by patterning the CNTs onto the cathode using catalyst masking, [123] lithography, [123] or screen-printing [112] while the anode is coated with a phosphor array which produces colored light when hit by an electron.…”
mentioning
confidence: 99%